The Mediating Role of Social Responsibility between Sustainability Accounting and Financial Performance - Mohammed, Basema Hazem (Journal of Economics and Administrative Sciences, 2025)
This research aims to identify the role of sustainability accounting in improving financial performance by adopting social responsibility indicators. The research aims to clarify how social responsibility can contribute to enhancing the financial benefits resulting from sustainability accounting practices, ultimately leading to improved financial performance of companies. A mixed-methods approach was employed to analyse both qualitative and quantitative data. A random sample of banks listed on the Iraq Stock Exchange was selected for the study, including five banks for a four-year time series, in addition to a sample of specialists for the purpose of answering the axes related to the qualitative variable of social responsibility indicators. A mixed model was formulated according to the MixMode method and tested by structural modelling. The research concludes that the impact of sustainability accounting appears through adopting the social responsibility model through several mechanisms such as focusing on economic efficiency, positive social relations and environmental compliance, which enhances the company’s sustainability, reduces risks, increases profitability and improves financial performance. Among the most important recommendations are: Developing a comprehensive sustainability policy that clarifies its commitment to complying with environmental and regulatory requirements, which should include the objectives, standards and procedures that will be followed to ensure compliance.